Laves phase precipitation in Ti-Zr-Fe-Cr alloys with high strength and large plasticity - Rabadia, C.; Liu, Y.; Wang, L.; Sun, Hongqi; Zhang, L. (Elsevier, 2018)
In this work, a novel serial of Ti-33Zr-xFe-yCr (x = 3, 5, 7 wt% and y = 2, 4 wt%) alloys was designed first with an expectation to obtain Laves phase in microstructure and then these alloys were produced using cold crucible levitation melting. Microstructure and phase analyses suggest the precipitation of a C15 type Laves phase with a dominating ß phase in all the Ti-33Zr-xFe-yCr alloys except in Ti-33Zr-3Fe-2Cr alloy which has a single ß phase microstructure. The volume fraction of the Laves phase increases upon increasing the Fe and Cr concentrations in Ti-Zr-Fe-Cr alloys. Mechanical properties evaluation reveals the highest ultimate compressive strength (~2 GPa) and superior plastic strain (33.6%) in Ti-33Zr-3Fe-4Cr alloy. Moreover, all the studied alloys exhibit extraordinarily high yield strength above 1 GPa and hardness exceeding 8 GPa. Embrittlement in Laves phase alloys, which is a common problem, is not encountered in this work as all the studied alloys display plastic strain including maximum elongation of 40%. The fracture behaviour of each studied alloy is also discussed in terms of the influence of Laves phase on a fracture, shear banding pattern and plastic deformation.